Transition-state analysis of the arginine-specific human ADP-ribosyltransferase 1 - Daniel P. Groom; Jennifer T. Aguilan; Amanda Lopacinski; Scott J. Garforth; Vern L. Schramm (Proceedings of the National Academy of Sciences, 2026)
The ADP-ribosylation of proteins is a versatile, reversible, posttranslational modification involved in the dynamic regulation of numerous cellular processes. Human ADP-ribosyltransferase 1 ( hs ART1, EC: 2.4.2.31) is a membrane-associated, GPI-anchored, mono-ADP-ribosyltransferase selective for mono-ADP ribosylation (MARylation) of L-arginine residues. Dysregulation of hs ART1 activity has been shown to permit immune cell evasion in non–small cell lung cancer (NSCLC) through elevated MARylation at Arg125 of the purinergic type 2 receptor (P2X7) in P2X7-positive T cells, resulting in NAD + -induced cell death (NICD) of tumor-penetrating immune cells. With hs ART1 emerging as an immunotherapy target in select cancers, there is a need to develop small-molecule inhibitors. The transition state (TS) for the MARylation of P2X7 peptide was determined from kinetic isotope effect (KIE) measurements of 3 H-, 14 C-, 18 O-, and 15 N-labeled NAD + substrates. Quantum mechanical (QM) calculations of the reaction coordinate, mapped with experimental KIEs, identify a TS geometry consistent with a highly dissociative, asymmetric, concerted mechanism with minimal contributions from the leaving group nicotinamide (NAM) and minor contributions from the incoming L-arginine guanidinium. The absence of a normal deuterium solvent isotope effect identifies a positively charged guanidinium nucleophile, leading to a dication N-ribosyltransferase mechanism. Together with the unusual, normal 18 O–O4 ′ KIE, we identified unique charge accumulation across the oxocarbenium at the TS caused by an increased bond order between the C1 ′ –C2 ′ , and decreased bond order between the C4 ′ –O4 ′ of the nicotinamide mononucleotide ribose. This is the first L-arginine-specific ADP-ribosylation TS to be characterized, a step toward the design of TS analogs.